Strategies for dose reduction with specific clinical indications during computed tomography. (October 2020) - Joyce, S.; O'Connor, O.J.; Maher, M.M.; McEntee, M.F.
Abstract: Increasing integration of computed tomography (CT) into routine patient care has escalated concerns regarding associated radiation exposure. Specific patient cohorts, particularly those with cystic fibrosis (CF) and Crohn's disease, have repeat exposures and thus have an increased risk of high lifetime cumulative effective dose exposures. Thoracic CT is the gold standard imaging method in the diagnosis, assessment and management of pulmonary disease. In the setting of CF, CT demonstrates increased sensitivity compared with pulmonary function tests and chest radiography. Furthermore, in specific cases of Crohn's disease, CT demonstrates diagnostic superiority over magnetic resonance imaging (MRI) for radiological evaluation. Low dose CT protocols have proven beneficial in the evaluation of CF, Crohn's disease and renal calculi, and in the follow up of testicular cancer patients. For individuals with chronic conditions warranting frequent radiological follow up, the focus must continue to be the incorporation of appropriate CT use into patient care. This is of particular importance for the paediatric population who are most susceptible to potential radiation induced malignancy. CT technological developments continue to focus on radiation dose optimisation. This article aims to highlight these advancements, which prioritise the acquisition of diagnostically satisfactory images with the least amount of radiation possible.